1999
DOI: 10.1111/j.1559-1816.1999.tb00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Reactions to the Drunk Driver: Associations With Intervention and Their Success1

Abstract: Research on psychological factors in helping behavior has been undertaken primarily in laboratory settings. Although this work has been instrumental in identifying psychological factors that influence helping, their role in naturally occurring helping behavior, such as informal drunk‐driving intervention, is largely unknown. College students (N= 192) completed a questionnaire that assessed 11 possible reactions to the drunk driving situation, types of interventions, and their success. Over half of the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Across the reviewed studies, few provided reference to the construct of personal responsibility; however the research did support the importance of responsibility in social intervention. Hernandez et al (1999) showed that greater rating of responsibility was associated with greater likelihood of an assertive intervention and that chivalry was associated with greater passive interventions (e.g. providing coffee).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Across the reviewed studies, few provided reference to the construct of personal responsibility; however the research did support the importance of responsibility in social intervention. Hernandez et al (1999) showed that greater rating of responsibility was associated with greater likelihood of an assertive intervention and that chivalry was associated with greater passive interventions (e.g. providing coffee).…”
Section: Resultsmentioning
confidence: 99%
“…Intervention strategies were also the focus of research by Shore and Compton (2000) rather than what predicts intervention. Of note, while intended intervention behavior was the outcome in a number of studies, other researchers limited the sample to those who have intervened and focused on past behavior (Hernandez et al, 1999; Labouvie & Pinsky, 2001; Mauck & Zagumny, 2000; Shore & Compton, 2000). Thus there are some studies examining intended behavior and other examining past behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations